2003
DOI: 10.1111/1539-6924.00384
|View full text |Cite
|
Sign up to set email alerts
|

Data Available for Evaluating the Risks and Benefits of MTBE and Ethanol as Alternative Fuel Oxygenates

Abstract: The wide-scale use of methyl tertiary butyl ether (MTBE) in gasoline has resulted in substantial public controversy and action to ban or control its use due to perceived impacts on water quality. Because oxygenates are still required under federal law, considerable research has focused on ethanol as a substitute for MTBE. In this article, we summarize the currently available literature on the air and water quality risks and benefits of MTBE versus ethanol as alternative fuel oxygenates. We find that MTBE-fuel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…[149,150] The process involves the reaction of isobutene with methanol in the presence of an acidic catalyst at 30 to 100 8C and 0.7 to 1.4 MPa in the liquid phase [Equation (11)]. [151] When biomethanol is used, the obtained MTBE cannot be fully considered a renewable biofuel because isobutene is typically derived from oil.…”
Section: Biomtbementioning
confidence: 99%
“…[149,150] The process involves the reaction of isobutene with methanol in the presence of an acidic catalyst at 30 to 100 8C and 0.7 to 1.4 MPa in the liquid phase [Equation (11)]. [151] When biomethanol is used, the obtained MTBE cannot be fully considered a renewable biofuel because isobutene is typically derived from oil.…”
Section: Biomtbementioning
confidence: 99%
“…Davis and Erickson [2] published recently a review paper analysing the different processes of bioremediation and natural attenuation of MTBE, concluding that not enough rigorous studies of MTBE bioremediation have been carried out yet in order to ensure that it is feasible under all conditions, and they state also that the times needed for these bioremediation processes are still to be determined precisely. Other literature references report on the other hand satisfactory examples of MTBE biodegradation [3,4], or establish a comparison between risks and benefits of MTBE as alternative fuel oxygenates and other commonly used alternatives, as for instance ethanol [5]. Thus, the convenience of the MTBE use still remains a controversial subject.…”
Section: Introductionmentioning
confidence: 99%
“…These finding are also consistent with the published literature in which median detected concentrations of MTBE were generally found to be quite low (i.e., less than 0.5 µg/L) based on a number of national, regional, and statewide assessments conducted over the last decade (Williams and Pierce, 2009). Previously published risk assessments have also concluded that MTBE drinking water exposures are not expected to pose a serious health threat to water consumers in California Percent detects 0.00% 0.00% 0.00% 0.00% 0.00% 0.00% 0.03% 0.04% 0.00% 0.00% 0.00% 0.00% 0.00% 0.10% 0.00% 0.02% A Includes wells with all types of water status (e.g., raw, treated, untreated, inactive, on-standby, abandoned, destroyed) 282 MTBE in California Water 283 or the United States (Williams et al, 2003b;Hartley et al, 1999;Stern and Tardiff, 1997). Third, evaluating the MTBE sampling data from a geographic perspective shows that MTBE detections are concentrated in specific geographic areas rather than widespread across the entire state.…”
Section: Discussionmentioning
confidence: 99%